Impact of Morphine Dependence and Withdrawal on the Reinforcing Effectiveness of Fentanyl, Cocaine, and Methamphetamine in Rats - Seaman Jr, Robert W.; Collins, Gregory T. (Frontiers in Pharmacology, 2021)
Recent estimates suggest increased popularity of the concurrent use of opioids and stimulants, with over 50% of treatment-seeking opioid users reporting regular stimulant use. The goal of the current study was to determine how opioid dependence and withdrawal affect the reinforcing effects of fentanyl, cocaine, and methamphetamine. Male Sprague-Dawley rats were allowed to self-administer fentanyl under a progressive ratio (PR) schedule of reinforcement. Baseline evaluations of reinforcing effectiveness of fentanyl, cocaine, and methamphetamine were determined. Opioid dependence was then established by administering escalating doses of morphine (10-40 mg/kg) twice-daily for four days and subsequently maintained by once-daily injections of 40 mg/kg morphine. To evaluate the impact of opioid dependence and withdrawal on the self-administration of fentanyl, cocaine, and methamphetamine, sessions occurred either 12 or 20 hours after the morphine, respectively. During opioid withdrawal, the fentanyl dose-response curve was shifted rightward with an increase in maximal effectiveness, whereas it was shifted rightward with a reduction in maximal effectiveness when evaluated in rats currently dependent on opioids, relative to baseline. The reinforcing effects of cocaine and methamphetamine were unchanged by either condition. The current studies provide direct evidence that the reinforcing effects of fentanyl are increased in opioid-withdrawn rats and reduced in opioid-dependent rats, relative to rats that are not physically dependent on opioids. These findings suggest that motivations to use opioids are dependent on the state of the individual whereas stimulants retain their reinforcing effects regardless of whether the individual is in an opioid-dependent or withdrawn state.